PEMBELAJARAN MATEMATIKA BERBASIS-MASALAH YANG MENGHADIRKAN KECERDASAN EMOSIONAL - Ibrahim Ibrahim (IKIP Siliwangi and I-MES, 2012)
Problem-based learning in the context of mathematics learning is a math learning strategies in the classroom with activities solve mathematical problems so that students can construct mathematical knowledge by himself. In connection with the efforts to achieve the learning objectives of mathematics through problem-based learning, of course, requires students to use the potential optimally. Meanwhile, to create mathematical learning process with the use of students' potential optimally, then the emotional intelligence of the students need to be a concern. Emotional considerations in mathematics learning in particular may be a bit much help in receiving math, in the middle of contention that still believed by most students, that math is a difficult subject. Thus, the presence of emotional intelligence can be seen as aspects to consider, it can even be used as the basis for follow-problem-based learning process well so that the achievement of mathematics learning in their entirety.